Feasibility and parametric study of a thermal- energy driven Reverse Osmosis system for Water Treatment in India. (August 2019) - Mudgal, A; Patel, V; Patel, J; Modi, B
Abstract: Reverse osmosis (RO) is the choice in most cases for its clean and trouble free operation in spite of the use of high-grade electric energy. The challenge with this process is increasing electricity cost and rejection of brine. We have modelled a new system which is capable to run RO module using low-grade thermal energy instead. A steam source drives a cylinder piston arrangement and this kinetic energy is transferred to another cylinder piston through a linkage mechanism. This energy finally is used to pressurize the saline water towards RO membrane. Steam may be generated from Solar or from a biomass boiler as available in rural areas of India. The results found so far are encouraging and indicates product water cost to be around 1.5 per m 3 by use of small design. Such designs may give a wide range of units capable of producing from few m 3 to hundreds of m 3 per day.